Superconducting magnetic energy storage system with an improved nonlinear control approach for pulsed power applications. (26th May 2020) - Penthia, Trilochan; Panda, Anup Kumar; Mohanty, Pratap Ranjan; Patnaik, Nishant
Summary: The electrical grid with pulsed power loads (PPLs) is of the significant interest in aerospace and marine applications. In this work, a Superconducting Magnetic Energy Storage (SMES)‐based Power Conditioning System (PCS) is proposed to compensate the pulsating load, and mitigates the adverse consequences of the load. A uniform source current and power with minimum variations is maintained irrespective of the PPL. A detrimental high rating stress on the system due to the load is substantially reduced by the proposed system. Particularly, this paper presents a nonlinear control approach based on Dynamic Evolution Control (DEC) for tight error regulation of the controlling parameters ( three‐phase compensating currents and DC‐link voltage ). The control scheme is implemented in both the inverter and DC‐DC converter of the PCS for an efficient energy exchange between the SMES coil and the grid. Moreover, a comparative performance of the control scheme is examined under two different modes of operation, that is, Shunt Active Power Filter (SAPF) and SMES‐based PCS mode. The proposed system is validated in MATLAB/Simulink and real‐timed SPACE1104 environment.